Bilateral basal ganglion haemorrhage in diabetic ketoacidotic coma: case report - Ertl-Wagner, Birgit; Jansen, Olav; Schwab, Stefan; Sartor, Klaus (Neuroradiology, 1999)
We report bilateral oedema and haemorrhagic transformation in the basal ganglia of a 59-year old woman with severe diabetic ketoacidosis. Lack of cerebral vascular autoregulation, followed by blood-brain barrier disruption due to the so-called breakthrough mechanism is presumed to be the cause.